Computational fluid dynamics validation and comparison analysis of scale‐up relationships of spouted beds. (5th August 2013) - Du, Wei; Xu, Jian; Wei, Weisheng; Bao, Xiaojun
Abstract A computational fluid dynamics (CFD) approach was attempted to investigate the hydrodynamic similarity of spouted beds of different sizes. The dimensionless scaling groups were derived by analysing the solid stress tensors with the kinetic theory of granular flow (KTGF). Results show that Ums, the minimum spouting velocity and the dimensionless spout diameter (Ds/Dc), become smaller with the increasing column diameter (Dc) as the fluid flares out to the annulus immediately above the orifice, and the portion of fluid in the annulus region increases with the increasing column diameter. Importantly, we observed distinctive dissimilarity in the voidage profiles and dimensionless particle velocities in the upper part of spouted beds, especially for larger columns. New correlations on spout diameter and Ums were derived based on the scaling‐up analysis by regression of experimental data appeared in literatures for both small and large columns, which can greatly improve the predictions for spouted beds as compared with those previous equations, especially for large columns with deviations less than 15% for most of data.